2018
DOI: 10.1177/1938640018816378
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Reverse Sural Fascio-Cutaneous Flap Outcomes in the Management of Foot and Ankle Soft Tissue Defects in Diabetic and Trauma Patients

Abstract: Introduction. Soft tissue defects in the distal leg and foot are challenging conditions for reconstruction. The widely used reverse sural fascio-cutaneous flap (RSFCF) has been reported with large variation in complication frequency. Some authors reported higher complications in the diabetic population when compared with trauma patients. We compared the reliability of the RSFCF in treating such defects among both populations. Methods. This is a retrospective series with a prospective data collection of 24 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 19 publications
(38 reference statements)
1
22
0
Order By: Relevance
“…7, Each included study had a majority of patients with one or more comorbidity, including diabetes mellitus, end-stage renal disease, hypertension, chronic osteomyelitis, or PVD. Seventeen studies only included patients with diabetes, 4,7,14,29,35,36,39,40,43,49,[53][54][55][56]59,60,65 five only included patients with PVD, 31,34,35,52,56 and three only included patients with chronic osteomyelitis. 43,44,47 ►Table 1 describes the number of studies that included patients with each comorbidity, the most prevalent being diabetes mellitus.…”
Section: Resultsmentioning
confidence: 99%
“…7, Each included study had a majority of patients with one or more comorbidity, including diabetes mellitus, end-stage renal disease, hypertension, chronic osteomyelitis, or PVD. Seventeen studies only included patients with diabetes, 4,7,14,29,35,36,39,40,43,49,[53][54][55][56]59,60,65 five only included patients with PVD, 31,34,35,52,56 and three only included patients with chronic osteomyelitis. 43,44,47 ►Table 1 describes the number of studies that included patients with each comorbidity, the most prevalent being diabetes mellitus.…”
Section: Resultsmentioning
confidence: 99%
“…Some interesting systematical reviews showed that trauma is the most common indication for soft tissue reconstruction with the RSAF in the lower leg. 10 , 13 , 14 More than 60% of sural flaps were indicated because of trauma of the distal leg. Unfortunately, it is not frequently well documented nor differentiated in the literature whether the trauma caused open fracture, osteomyelitis, exposed osteosynthesis material, or only exposed soft tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the free flap technique is not devoid of risks, mostly in a patient with diabetes. Assi et al 16 demonstrated that diabetes itself is not a risk factor for the outcome of a free flap, but we must consider that this procedure may entail the sacrifice of one leg’s artery in a patient with a considerable risk of developing a diabetic foot. 17 …”
Section: Discussionmentioning
confidence: 99%